A nitric oxide releasing self-assembled peptide amphiphile nanomatrix for improving the biocompatibility of microporous hollow fibers - El-Ferzli, George T (ASAIO J, 2015)
Oxygenators are critical components of extracorporeal circuits used frequently in cardiopulmonary bypass and intensive care, but platelet activation and induction of a complex inflammatory response are usually observed with their use. To improve the biocompatibility of oxygenators, we developed a nitric oxide (NO)-releasing, self-assembled peptide amphiphile nanomatrix. The nanomatrix formed a homogenous coating over the microporous hollow fibers as demonstrated by scanning electron microscopy. We quantitated platelet adhesion to the artificial fibers by measuring absorbance/area of platelets (Abs/A; nm/m(2)) using acid phosphatase assay. There was a 17-fold decrease in platelet adhesion to the nanomatrix (Abs/A = 0.125) compared to collagen controls (Abs/A = 2.07; p<0.05) and a 22-fold decrease compared to uncoated fibers (Abs/A = 2.75; p<0.05). Importantly, the nanomatrix coating did not impede oxygen transfer in water through coated and uncoated fiber modules (p>0.05) in a bench top test circuit at different flow rates as estimated by change in partial pressure of oxygen in relation to water velocity through fibers. These findings demonstrate the feasibility of coating microporous hollow fibers with a NO-releasing, self-assembled amphiphile nanomatrix that may improve the biocompatibility of the hollow fibers without affecting their gas exchange capacity.